Borehole disposal of spent fuel and other high-level wastes: the case for deep, vertical, fully cased holes in saturated “hard” rock - Gibb, Fergus; Beswick, John; Travis, Karl (Frontiers in Nuclear Engineering, 2024)
Driven by major advances in deep drilling technology and the geological understanding of the deep continental crust over the past 70 years, disposal in deep boreholes has moved from being technically unachievable to the point that it now offers a viable solution for the most hazardous nuclear wastes that could effectively be implemented 'tomorrow', i.e., within a few years. Moreover, it is arguably superior in almost every respect to the mined and engineered repositories being pursued for high level wastes by most countries. During the first 50 years of their evolution almost all deep borehole disposal concepts shared five key aspects, namely -(i) the hole was as deep as possible, (ii) it was vertical, (iii) it was fully-cased and (iv) it was in 'hard' basement rock (v) saturated with aqueous fluid (groundwater). Technical advances in drilling over the last 20 years have encouraged proposed versions of the concept which depart from one or more of these aspects, but it is our contention that all five of the fundamental aspects should be retained. This paper summarises the more important arguments supporting this view. In order to meet the necessary post-closure (radiological) safety requirements, engineer out possible operational problems during construction and waste-package deployment and capitalise on the main benefits of borehole disposal, it is concluded the hole itself must be over 3 km deep, vertical, fully cased and in suitable hard (ideally granitic) host rock saturated with aqueous fluid.